Physiological plant ecology - Larcher, Walter (Springer-Verlag, 1995)
This book is the science of plant function in interaction with the environment with the contents: The Environment of plant; Carbon utilization and dry matter production; the Utilization of mineral elements; Water relations; Environmental Influences on Growth and Development; Plants under stress